Low Birth Weight Babies Born to Mothers Admitted to Gynecology and Obstetrics Department of Dhaka Medical College Hospital - Nessa, Zebun; Zaman, Iffat; Ferdous, Menoka; Rahman, Sumana; Das, Debalina (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: World health organization estimates that 25 million low birth weight (LBW) babies are born annually worldwide and 95% occur in developing countries. Low birth weight is a major public health problem of Bangladesh. So an attempt was made to study the incidence of low birth weight (<2.5kg) and also the associated risk factors of low birth weight among the new born babies born to Dhaka Medical College Hospital. Aims: To determine the Prevalence of low weight among the babies born and to determine the relationship of low birth weight with maternal factor like maternal weight, height, gestational period, antenatal checkup, heavy physical work during pregnancy, hypertension, age of the mother and parity, in Obs. & Gynae Department, DMCH. Method: This descriptive cross sectional study was done in Gynecology and Obstetrics Department of Dhaka Medical College Hospital. Five hundred (500) samples were selected for the study. The study was done from 1st January 2006 to 31 December 2006. Data processing and questionnaire are processed manually using scientific calculator and by computer using SPSS programmers version-16. All abortions, still born, gross congenital abnormalities were excluded from this study. The cut off point used for low birth weight is 2.5 kg. Results: A total of 500 women were interviewed. The incidence of low birth were found 21.6%. Younger than 20 yrs (31.25%) and more than 40 years (35.71%) mother delivered more low birth weight babies. The primigravida and multigravida (>4 parity) showed more low birth weight babies. Women from low socioeconomic condition produced significantly larger number of low birth weight babies as well as short stature. Low maternal height, less educated, illiterate, manual worker mother delivered more low birth weight babies. Preterm birth comprises larger number of low birth weight (LBW 35%). Low height of new born babies also associated with low birth weight. Female babies were higher than the male babies. Preterm babies were lighter (LBW) than the full term babies. Conclusion: The study finds out the incidence of low birth babies, the figure close to the developing countries. The study revealed that maternal age, gestational age, parity, socioeconomic status, maternal weight and disease condition have strong relations with birth weight of babies. Occupation and antenatal check up also affects birth weight of babies. J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 16-22